Analytical Chemistry Applied to Emerging Pollutants - Vaz Jr., Sílvio (Springer International Publishing, 2018)
This book addresses the highly relevant subject of emerging pollutants, which are especially alarming since most of the available treatment technologies are unable to degrade them. It discusses the sources of these pollutants and their fate in the environment, and the main tools available for their analysis. It also describes the representative environmental matrices (air, soil and water) and appropriate analytical methods for each matrix. Furthermore, it examines aspects of toxicology, chemometrics, sample preparation and green analytical chemistry. As such, it provides a broad overview of the potential analytical approaches for monitoring and controlling emerging pollutants. This book fills a gap in the literature, and is a valuable resource for all professionals concerned with emerging pollutant control in real-world situations. .